(3eLdS aj MOjK LGHQ GdPi QMd ajg eSjQI TgQ Edi YHO Gddg Hf CfjS QVi Gddg YfgeGs - (3TeS GdOjf eMeO Hf YHO Gddg Hf eMeO GdbjSi GdOeTbj GdeYQha HGHf fGUQ GdOjf,J (B842 (3g` s
(3ChdgG (B:s
(3CNHQJfG GdTjNI GdUGdMI GdCUjdI TeS Gdedhc HfJ GdfGUQ GHf TGPi HbQGAJi YdjgG s
(3BNQgG (B:s
(3dGJYLHf HeGd Sha JJQcg aEfeG gPg GdOfjG ehGQjK BNQN GdeLdS ai MOjK LGHQ GdPi QMd ai eSjQI TgQ Edi YHO Gddg Hf CfjS QVi Gddg JYGdi YfgeG s
(3HgG fXGe GdJYbjHIs
(3cJHJ HNW eged GdfbW CMjGfkG fbdkG Yf fSNI HNW GdeDda s
(3hYdi MGTjI fSNJfG SeGY HNW GdeDda hHBNQgG SeGY SfI (B837 (3Ydi GdeDda ef YOI YdeGA efge GdfGSN hTgO GdeDda Ydjg hELGRI HNWg s
(3hUaMI GdZdGa CjVkG HNW GdeDdas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
Keywords: (3GdMOjK h GdeUWdMs